Automated monitoring of activated sludge using image analysis - Motta, Maurício da (2000)
An automated procedure for the characterisation by image analysis of the morphology of activated sludge has been used to monitor in a systematic manner the biomass in wastewater treatment plants. Over a period of one year, variations in terms mainly of the fractal dimension of flocs and of the amount of filamentous bacteria could be related to rain events affecting the plant influent flow rate and composition.